‘The Jade Box Writings Newly Translated for Various Occasions’: a Fragment of One Mongolian Translation from the Aldan Maadyr National Museum of the Tyva Republic Revisited - Bembya L. Mitruev (Монголоведение, 2019)
Goals. The article seeks to introduce into scientific discourse a Mongolianlanguage text dealing with divination and astrological practices, and housed by the National Museum of the Tyva Republic (М-653). Materials. The Classical Mongolian manuscript text is a fragment (introductory part) of the famous Chinese composition titled ‘Jade Box Writings’. It includes 25 yellowish pages of medium size, the pages 7б, 9а, 9б, 10а, 10б missing from the document. The fragment comprises several sections dealing with astrology and divination. Results. The paper compares the Tuva-based text (М-653) to a woodblock print from the Institute of Oriental Manuscripts (ID no. F 145). The analysis reveals that manuscript М-653 contains a number of omissions (words and phrases), many lexemes having been essentially marred. The study concludes the Mongolian translation — as is evident from the title ‘A Concise Description of Chapter One of The Jade Box Writings Newly Translated for Various Occasions’ — is a concise translation of the Chinese original, the former missing quite a number of details, and suggests the Tuva-based manuscript is a copy of the Beijing Mongolian-language edition two xylographs of which have been discovered at the Institute of Oriental Manuscripts. The text introduced into scientific discourse is actually a historical document providing insight into household activities and worldview concepts of the 19th-century Mongols. The article transliterates the text, translates it into Russian, and supplements a facsimile.